The year in review: advances in interventional cardiology in 2019. (July 2020) - Galougahi, Keyvan Karimi; Petrossian, Gregory; Stone, Gregg W.; Ali, Ziad A.
Abstract : Purpose of review: Major studies in interventional cardiology in 2019 have added substantial new evidence for pharmaco-invasive management of coronary artery disease. The review highlights the main findings of a selection of these trials and summarizes their impact on clinical practice. Recent findings: Recent randomized studies examining the efficacy of revascularization or medical treatment in stable ischemic heart disease (SIHD), treatment of acute coronary syndromes, emerging interventional devices, adjunctive pharmacotherapy, and intravascular imaging and physiology guidance have substantially advanced the evidenced-based knowledge in interventional cardiology. Summary: Patients with SIHD and at least moderate myocardial ischemia have similar event-free survival after an initial conservative strategy of optimal medical therapy versus an upfront invasive strategy. Quality of life and angina-free status are significantly improved with revascularization. Percutaneous coronary intervention (PCI) and coronary artery bypass grafting provide similar 5-year outcomes in patients with left main coronary artery disease and low or intermediate disease complexity. An initially conservative management is equally effective as an early invasive approach in patients with out-of-hospital cardiac arrest without ongoing ischemia. Patients with ST-segment elevation myocardial infarction and multivessel disease benefit from staged complete revascularization after primary PCI. Post-PCI, patients with atrial fibrillation requiring anticoagulation can safely and effectively be treated with P2Y12 inhibitor monotherapy without aspirin. Lastly, intravascular imaging guidance improves post-PCI outcomes, warranting increased use in clinical practice.